Isolated Myocardial Bridging and Exercise-Related Cardiac Events - Gowd, B. M. P.; Thompson, P. D. (International Journal of Sports Medicine, 2014)
Myocardial bridging, which is defined as cardiac muscle overlying a part of a coronary artery, is the most common congenital coronary artery anomaly. Myocardial bridging is usually benign, but has been associated with exercise-related cardiac events. Guidelines for athletic participation in these patients are primarily based on reports from the general population with myocardial bridging. We performed a systematic literature search of PubMed, Ovid and Google Scholar for articles addressing exercise-related cardiac events associated with myocardial bridging. We identified 69 cases of which only 35 were well defined. We conclude that there are insufficient data to form definitive guidelines as to how physically active individuals with myocardial bridging should be managed. Prudence suggests that management should be individualized for those with possible symptoms. Beta adrenergic blockade is recommended as initial medical therapy. Surgery should be restricted to those with continued symptoms despite beta blocker therapy. There is no evidence that asymptomatic individuals without clinical evidence of ischemia should be restricted from vigorous activity.
Keywords: exercise; sports; athletes; myocardial Bridging